2019
DOI: 10.1002/ajpa.23897
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐transmitted helminth infection and intestinal inflammation among the Shuar of Amazonian Ecuador

Abstract: Objectives: Little research exists documenting levels of intestinal inflammationamong indigenous populations where exposure to macroparasites, like soil-transmitted helminths (STHs), is common. Reduced STH exposure is hypothesized to contribute to increased prevalence of elevated intestinal inflammation in wealthy nations, likely due to coevolutionary histories between STHs and human immune systems that favored anti-inflammatory pathways. Here, we document levels of intestinal inflammation and test association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 76 publications
1
30
2
Order By: Relevance
“…These findings among the Shuar are noteworthy because Shuar generally have low levels of inflammatory biomarkers and no evidence of chronic inflammation compared to WEIRD populations (Cepon‐Robins et al, 2019; McDade et al, 2012), suggesting that environmental factors, like pathogen exposure, are regulating immune function. This, however, cannot be accounted for by pathogen exposure alone, since other indigenous populations like the Tsimane have both high parasite loads and high CRP (Blackwell et al, 2016), indicating that more population‐based research needs to be conducted to fully understand these relationships.…”
Section: Why Is Autoimmunity Of Interest To Human Biologists?mentioning
confidence: 90%
See 3 more Smart Citations
“…These findings among the Shuar are noteworthy because Shuar generally have low levels of inflammatory biomarkers and no evidence of chronic inflammation compared to WEIRD populations (Cepon‐Robins et al, 2019; McDade et al, 2012), suggesting that environmental factors, like pathogen exposure, are regulating immune function. This, however, cannot be accounted for by pathogen exposure alone, since other indigenous populations like the Tsimane have both high parasite loads and high CRP (Blackwell et al, 2016), indicating that more population‐based research needs to be conducted to fully understand these relationships.…”
Section: Why Is Autoimmunity Of Interest To Human Biologists?mentioning
confidence: 90%
“…Previous research in human biology has shown that parasite exposure may reduce both systemic and local inflammation (Cepon‐Robins et al, 2019; Robins, 2015). Work among the Shuar of Amazonian Ecuador showed that adults who were infected with Ascaris lumbricoides (i.e., intestinal parasitic large roundworm) had significantly lower CRP levels (Robins, 2015).…”
Section: Why Is Autoimmunity Of Interest To Human Biologists?mentioning
confidence: 99%
See 2 more Smart Citations
“…S100A8/A9 has been previously investigated as marker for intestinal inflammation with controversial results so far [67,68]. A negative association between children infected with the intestinal helminth Trichuris trichiura and decreased intestinal inflammation as well as decreased concentration of S100A8/A9 compared to uninfected children has been reported [69]. In contrast, there was no evidence of an association between S100A8/A9 levels and Schistosoma mansoni [70] or Ascaris lumbricoides infection [71].…”
Section: Discussionmentioning
confidence: 99%